AN ARCHITECTURAL SYMMETRY IN BATAK TOBA TRADITIONAL HOUSES: A GEOMETRIC EXPLORATION - Aulia Simanjuntak; Fuzi Anggriani; Indah Christine; Samuel Sianturi; Maria Margaretha (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This research explores the concept of geometry in the architectural symmetry of Toba Batak traditional houses. The main focus is on the symmetry patterns that exist in the layout, decoration and structural elements of this traditional house. This research aims to investigate the concept of geometric symmetry in Toba Batak traditional houses, with a focus on cultural values, philosophy and visual harmony reflected in architectural design. Data was obtained through literature studies which included scientific journals, books, articles and previous research. The results of this research not only provide a deeper understanding of Indonesia's rich culture, but also have the potential to contribute to the preservation of Toba Batak traditional houses and cultural heritage as a whole. By understanding the role of geometric symmetry in this traditional house, this article opens insight into how this element is an integral part of the architectural heritage of the Toba Batak tribe, explores deeper cultural values, and introduces new literature in the context of traditional Indonesian architecture.